Análise da resposta de anticorpos IgE, IgG1 e IgG4 específica a antígenos derivados de grãos de pólen de Lolium multiflorum por ELISA e immunoblotting e diagnóstico de alergia por microarray de alérgenos em pacientes com polinose - Moreira, Priscila Ferreira de Sousa (2010)
In Southern Brazil, Lolium multiflorum pollen is thought to be the most important source for grass pollen allergy. The sensitivity of Brazilian grass pollen allergic patients to individual allergen molecules has not been analyzed yet. The aims of this work were, in the study I: to evaluate the IgE, IgG1 and IgG4 reactivity to the components of L. multiflorum pollen extract in grass pollen allergic patients; and in the study II: to evaluate the cross-reactivity between allergens from Lolium multiflorum and Phleum pretense pollen extracts and to use micro-arrayed allergen molecules to characterize IgE reactivity in Brazilian grass pollen allergic patients. In the study I, extract from Lolium multiflorum pollen was prepared and analyzed by SDS-PAGE. Serum samples from 33 patients with grass pollen allergy (Lm+) and 10 non atopic individuals (NA) were tested to the IgE, IgG1 and IgG4 reactivity by ELISA and immunoblotting. In the study II, sera from 78 grass pollen allergic patients and from 5 patients allergic to house dust mites (controls) were analyzed. To investigate the level of cross-reactivity, ELISA and immunoblotting inhibition experiments with Lolium multiflorum and Phleum pratense extracts were performed. The presence of IgE antibodies specific for 103 purified natural and recombinant allergens was investigated using allergen chips. In the study I, levels of IgE and IgG4 were significantly higher in the Lm+ group that showed IgE levels significantly higher than IgG1 (p < 0,0001) and IgG4(p < 0,01). Positive correlations were observed mainly between levels of IgE and IgG4 (rs = 0,61; p = 0,0001), with double positive association of 79% and single positive of 21% only to IgE. By SDS-PAGE, protein fractions were visualized in the range of 10 to 101 kDa. In the Lm+ group, the immunodominant components (>50%) for IgE were: 10, 20, 24, 26, 29, 32, 35, 37, 47, 54 and 57 kDa; for IgG1: 10, 24, 26, 29, 32, 54, 57 and 71 kDa; and for IgG4: 26, 29, 32, 54 and 57 kDa. In the NA group, reactivity was observed only to IgG4 (less than 50%) in the protein fractions of 29, 32, 37, 54 and 57 kDa, and for IgG1 (>50%) in the fractions of 29, 32, 54 and 71 kDa. In relation to study II, within the Brazilian grass pollen allergic patients, the most frequently recognized allergens were Phl p 1 (95%), Cyn d 1 (85%), Phl p 5 (82%), Phl p 2 (76%), Phl p 4 (64%) and Phl p 6 (45%). Most patients were sensitized only to grass pollen allergens. A high degree of IgE cross-reactivity between Phleum pratense and Lolium multiflorum was found. Immunobloting results showed that serum IgE recognized mainly L. multilflorum allergens and P. pratense extract did not completely inhibit serum IgE binding to L. multiflorum allergens. In conclusion, antigenic components from Lolium multiflorum pollen extract are able to induce IgE, IgG1 and IgG4 responses in grass pollen allergic patients, and also IgG1 and IgG4 responses in non atopic patients, but in lower levels. Antigenic components of 26, 29 and 32 kDa were recognized by IgE, IgG1 and IgG4 antibodies in patients with grass pollen allergy, in a higher frequency to IgE and IgG4. Component-resolved analysis of sera from Brazilian grass pollen allergic patients reveals an IgE recognition profile compatible with a preferential mono-sensitization to Lolium multiflorum pollen allergens. Due to the high degree of cross-reactivity between Phleum pratense and Lolium multiflorum allergens it seems that diagnosis can be achieved with timothy grass pollen allergens in the studied population.